Multifunctional flexible transparent conductive film and preparation method thereof

By adopting a combined structure of polyethylene terephthalate base layer and multi-layer MXene and silver nanowires in the conductive film, the problems of high resistance and poor adhesion of the conductive network are solved, and the high performance preparation of flexible transparent conductive films is achieved, with excellent photoelectric, electrical, and electromagnetic shielding properties.

CN119852009AInactive Publication Date: 2025-04-18QIDONG ZHENCAI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510346594.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the method of preparing conductive films is limited due to the random stacking state of the silver nanowire network, due to the high resistance of the conductive network and poor adhesion of the conductive material.

Method used

The conductive layer structure consisting of the first auxiliary conductive layer of MXene, the main conductive layer of silver nanowires, and the second auxiliary conductive layer of MXene, is self-assembled layer by layer by spin coating method, and combined with heating treatment to improve the conductivity and adhesion of the film.

Benefits of technology

The flexible transparent conductive film is prepared, with excellent photoelectric and electric heating properties, can quickly reach high temperatures at low voltages, and has good electromagnetic shielding efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852009A_ABST
    Figure CN119852009A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional flexible transparent conductive film and a preparation method thereof, and belongs to the technical field of nanometer material science and engineering, the multifunctional flexible transparent conductive film based on Ti3C2Tx-MXene and silver nanowires comprises a polyethylene glycol terephthalate substrate layer and a conductive layer, the conductive layer sequentially comprises an MXene first auxiliary conductive layer, a silver nanowire main conductive layer and an MXene second auxiliary conductive layer from bottom to top; the preparation method of the conductive thin film comprises the following steps: S1, preparing a substrate layer: putting a polyethylene glycol terephthalate thin film into a polyvinylpyrrolidone aqueous solution, and stirring for 0.5-1 hour at 60-80 DEG C; and S2, sequentially spin-coating the prepared MXene, the silver nanowire and the MXene on a PET (Polyethylene Terephthalate) substrate to obtain the flexible transparent conductive thin film. The problems that in the prior art, due to the random stacking state of the silver nanowire network, the resistance of the conductive network is high, and the adhesiveness of the conductive material is poor are solved. The method has the advantages of good conductivity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nanomaterial science and engineering technology, and in particular to a multifunctional flexible transparent conductive film and a preparation method thereof. Background Art

[0002] Electrothermal materials are widely used in certain conditions in our lives. They can convert electrical energy into thermal energy through Joule heating or resistance heating when electricity is applied. Traditionally, indium tin oxide (ITO) has attracted a lot of research interest due to its low resistance and good light transmittance. Unfortunately, its fragility under mechanical deformation, low acid and alkali resistance, lack of indium, and complex manufacturing process have limited its widespread application in electrothermal materials.

[0003] With the work of researchers such as Yury Gogotsi and Zhou, Ti 3 C 2 T x - MXene and silver nanowires (AgNW) and other nanomaterials have gradually come into people's view and have been used more and more. Nanomaterials are one of the best candidates for electrothermal materials because of their excellent flexibility, light weight, good stability, high conductivity, and high electrothermal conversion efficiency. Since the silver nanowire network is generally in a randomly stacked state, the loose contact between the wires makes the conductive network have a high resistance, which is not conducive to conductivity and stability. In addition, the properties of some substrate materials are different from those of the conductive material, so the conductive material cannot be well attached to the substrate; the above problems limit the method of preparing conductive films.

[0004] Therefore, there is an urgent need for a multifunctional flexible transparent conductive film and a preparation method thereof, so that the obtained electric heating film exhibits excellent photoelectric and electrothermal properties, has high electrothermal conversion efficiency, and has a wide range of applications in the electrothermal field. Summary of the invention

[0005] To this end, the present invention provides a multifunctional flexible transparent conductive film and a preparation method thereof to solve the problems in the prior art of high conductive network resistance and poor conductive material adhesion caused by the random stacking state of the silver nanowire network.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: According to a first aspect of the present invention, a multifunctional flexible transparent conductive film is provided, comprising a polyethylene terephthalate substrate layer and a conductive layer, wherein the conductive layers are, from bottom to top, a MXene first auxiliary conductive layer, a silver nanowire main conductive layer and a MXene second auxiliary conductive layer.

[0007] According to a second aspect of the present invention, there is provided a method for preparing a multifunctional flexible transparent conductive film, comprising the following steps: S1. Preparation of substrate layer: placing a polyethylene terephthalate film in a polyvinyl pyrrolidone aqueous solution, stirring at 60-80° C. for 0.5-1 h, hydrophilizing the polyethylene terephthalate film, and after the reaction is completed, washing the polyethylene terephthalate film with anhydrous ethanol and deionized water and drying it to prepare a polyethylene terephthalate substrate for standby use; S2. Preparation of conductive layer: Spin-coat MXene solution, silver nanowire solution and MXene solution layer by layer on the surface of polyethylene terephthalate substrate layer, and dry on a heating table to obtain a transparent and flexible conductive film.

[0008] Furthermore, the molecular weight of polyvinyl pyrrolidone used in S1 is 1300000, and the concentration of the prepared aqueous solution is 1-4wt%.

[0009] Furthermore, the MXene nanosheets used to prepare the MXene solution in S2 are Ti 3 C 2 T x .

[0010] Further, Ti is prepared in S2 3 C 2 T x The specific steps of -MXene are as follows: (1) adding lithium fluoride powder into a polytetrafluoroethylene beaker containing a hydrochloric acid solution and stirring to prepare a precursor etching solution; (2) Weighing aluminum titanium carbide quantitatively, and adding it to the precursor etching solution in small amounts and multiple times, placing the reaction system in a 40°C water bath, stirring continuously, to obtain a mixed solution; (3) Add a certain amount of deionized water to the obtained mixed solution and centrifuge it. Pour out the separated supernatant, add deionized water again and shake it to mix with the viscous material at the bottom. Continue centrifugation. Repeat the operation until the pH of the supernatant is >6, and collect the supernatant.

[0011] Furthermore, in step (3), the centrifugal speed is 1500-3500 rpm, and the centrifugal time is 3-5 min.

[0012] Furthermore, the preparation method of the silver nanowire solution in S2 is: (1) Dissolve polyvinyl pyrrolidone in ethylene glycol, then add silver nitrate. After the silver nitrate is completely dissolved, transfer the resulting liquid to a flask and heat it in an oil bath; (2) Under magnetic stirring, slowly add sodium chloride and sodium bromide, then stir to mix, let stand to react, and cool to room temperature after the reaction is complete; (3) adding acetone to the silver nanowires to cause them to aggregate and settle, filtering out particles and impurities, and dispersing the silver nanowires in a 0.5 wt % polyvinyl pyrrolidone aqueous solution, repeating this process 3-5 times to obtain purified silver nanowires; (4) Disperse the purified silver nanowires in anhydrous ethanol and prepare the required concentration for later use.

[0013] Furthermore, in step (2), the concentration of sodium chloride is 22-54 mM, and the concentration of sodium bromide is 10-27 mM.

[0014] Furthermore, the spin coating speed of the MXene solution in S2 is 4000-5000 rpm for 20-50 s, and the spin coating speed of the silver nanowires is 3000-5000 rpm for 30-50 s.

[0015] Furthermore, the concentration of the MXene solution is 0.1-0.5 mg / mL, and the concentration of the silver nanowire solution is 2-4 mg / mL.

[0016] The present invention has the following advantages: 1. The polyethylene terephthalate film is hydrophilically modified by using a polyvinyl pyrrolidone aqueous solution, and the polyvinyl pyrrolidone molecules are adsorbed on the surface of the polyethylene terephthalate film through van der Waals forces. The lactam in the polyvinyl pyrrolidone molecule is a strong polar group and has hydrophilicity; and the MXene nanosheets with -O, -F, -OH groups as end groups also have strong hydrophilicity and electronegativity. Therefore, the polyethylene terephthalate film treated with a polyvinyl pyrrolidone aqueous solution shows good hydrophilicity, which effectively improves the adhesion with the conductive material, and MXene can also better adhere to the surface of the polyethylene terephthalate film substrate that has been hydrophilically treated.

[0017] 2. This application can make the conductive network more stable and provide more additional conductive paths by sandwiching silver nanowires between MXene nanosheets. The preparation process of the self-assembled film is simple and the cycle is short. The film has excellent photoelectric properties and can reach a steady-state temperature of 85°C in a short time at a low voltage of 5V. The maximum electromagnetic shielding efficiency is 33.6dB in the frequency range of 8.2-12.4GHz.

[0018] 3. The topmost MXene nanosheet in the conductive layer of the present application welds the silver nanowires through capillary force, thereby improving the stability and conductivity of the silver nanowires at the overlap and protecting the silver nanowires from oxidation by air.

[0019] 4. This application uses an improved polyol method to prepare silver nanowires with an average diameter of 36 nm and an average length of 32 μm, with an aspect ratio of up to 888, and adopts a full solution method to allow the conductive material to self-assemble layer by layer on the surface of the polyethylene terephthalate substrate during the spin coating process, thereby constructing a conductive network with a sandwich structure, and the photoelectric properties of the conductive film can be adjusted by adjusting the concentration of the silver nanowire solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0021] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0022] Figure 1 A schematic diagram of the preparation process of the MXene / AgNWs / MXene conductive film provided by the present invention; Figure 2 A transmission electron microscope image of the MXene provided by the present invention; Figure 3 A scanning electron microscope image of the silver nanowires provided by the present invention; Figure 4 The time-temperature curve of the MXene / AgNWs / MXene conductive film provided by the present invention at different voltages; Figure 5 The temperature change trend of the MXene / AgNWs / MXene conductive film provided by the present invention every 3 minutes, with a fixed step voltage of 1V and a voltage range of 1-5V; Figure 6 Cyclic electric heating test curve of the MXene / AgNWs / MXene conductive film provided by the present invention at 2V and 4V; Figure 7 The shielding effectiveness of the MXene / AgNWs / MXene conductive film provided by the present invention at 8.2-12.4 GHz; Figure 8Power coefficients of absorption, reflection and transmission of MXene / AgNWs / MXene conductive film at 8.2-12.4 GHz. DETAILED DESCRIPTION

[0023] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides a multifunctional flexible transparent conductive film, comprising a polyethylene terephthalate (PET) substrate layer and a conductive layer, wherein the conductive layers are, from bottom to top, a MXene first auxiliary conductive layer, a silver nanowire (AgNWs) main conductive layer and a MXene second auxiliary conductive layer.

[0025] The present invention provides a method for preparing a multifunctional flexible transparent conductive film, comprising the following steps: S1. Preparation of the substrate: Place a polyethylene terephthalate (PET) film in a polyvinyl pyrrolidone (PVP) aqueous solution and stir at 60-80°C for 0.5-1h to perform a hydrophilic treatment on the polyethylene terephthalate (PET) film. After the reaction is completed, place the polyethylene terephthalate (PET) film in anhydrous ethanol (C 2 H 6 O) and deionized water (H 2 O) cleaning and drying to prepare a polyethylene terephthalate (PET) substrate for standby use; S2. Preparation of conductive layer: MXene solution, silver nanowire (AgNWs) solution and MXene solution were spin-coated layer by layer on the surface of polyethylene terephthalate (PET) substrate layer, and dried on a heating table at 120 °C to obtain a flexible transparent conductive film with high light transmittance and low resistance, such as Figure 1 shown.

[0026] Specifically, the molecular weight of polyvinyl pyrrolidone (PVP) used in S1 is 1300000, and the concentration of the prepared aqueous solution is 1-4 wt %.

[0027] Among them, the MXene nanosheets used to prepare the MXene solution in S2 are Ti 3 C 2 T x .

[0028] Among them, the Ti used in preparing MXene solution in S23 C 2 T x The specific steps of -MXene are as follows: (1) adding lithium fluoride (LiF) powder into a polytetrafluoroethylene beaker containing a hydrochloric acid (HCl) solution and stirring to prepare a precursor etching solution; (2) Quantitatively weigh titanium aluminum carbide (Ti 3 AlC 2 ), and add it to the precursor etching solution in small amounts and multiple times, place the reaction system in a 40°C water bath, and stir continuously to obtain a mixed solution; (3) Add a certain amount of deionized water (H 2 O) and centrifuged, the separated supernatant was poured out, and deionized water (H 2 O) and then shake to mix with the viscous material at the bottom, continue centrifugation, repeat the operation until the pH of the supernatant is > 6, collect the supernatant, such as Figure 2 shown.

[0029] Specifically, in step (3), the centrifugal speed is 1500-3500 rpm, and the centrifugal time is 3-5 min.

[0030] The preparation method of the silver nanowire (AgNWs) solution in S2 is as follows: (1) Dissolve polyvinyl pyrrolidone (PVP) in ethylene glycol (C 2 H 6 O 2 ), and then silver nitrate (AgNO 3 ), wait for silver nitrate (AgNO 3 ) After it is completely dissolved, the resulting liquid is transferred to a flask and heated in an oil bath; (2) Under magnetic stirring, slowly add sodium chloride (NaCl) and sodium bromide (NaBr), then stir to mix, let stand to react, and cool to room temperature after the reaction is complete; (3) Add acetone (CH 3 COCH 3 ), the silver nanowires (AgNWs) aggregate and settle, and after filtering out the particles and impurities, the silver nanowires (AgNWs) are dispersed in a 0.5wt% polyvinyl pyrrolidone (PVP) aqueous solution, and the purification process is repeated 3-5 times to obtain purified silver nanowires (AgNWs), such as Figure 3 As shown; (4) Disperse the purified silver nanowires (AgNWs) in anhydrous ethanol (C 2 H 6 O) and prepare the required concentration for later use.

[0031] Specifically, in step (2), the concentration of sodium chloride (NaCl) is 22-54 mM, and the concentration of sodium bromide (NaBr) is 10-27 mM.

[0032] Specifically, the spin coating speed of the MXene solution in S2 is 4000-5000 rpm for 20-50 s, and the spin coating speed of the silver nanowire (AgNWs) solution is 3000-5000 rpm for 30-50 s.

[0033] Specifically, the concentration of the MXene solution is 0.1-0.5 mg / mL, and the concentration of the silver nanowire (AgNWs) solution is 2-4 mg / mL.

[0034] The reagents and materials used in the present invention are: polyethylene terephthalate (PET) film, polyvinyl pyrrolidone (PVP), ethylene glycol (C 2 H 6 O 2 ), deionized water (H 2 O), anhydrous ethanol (C 2 H 6 O), lithium fluoride (LiF), hydrochloric acid (HCl), titanium aluminum carbide (Ti 3 AlC 2 ), sodium chloride (NaCl), sodium bromide (NaBr), silver nitrate (AgNO 3 ), acetone (CH 3 COCH 3 )wait.

[0035] In the present invention, a Keithley 2700 four-probe resistance meter was used to measure the resistance of the flexible transparent conductive film. A transmission electron microscope (TEM) was used to characterize the morphology of the prepared MXene nanosheets. A thermocouple was used to test the temperature change of the electric heating film. A vector network analyzer (Agilent E5071C) was used to measure the electromagnetic shielding performance of the flexible transparent conductive film at 8.2-12.4 GHz.

[0036] Example 1 S1. Preparation of substrate layer: Place polyethylene terephthalate (PET) film in 2 wt% polyvinyl pyrrolidone (PVP) aqueous solution, stir at 80 °C, 500 rpm for 1 h, hydrophilize the polyethylene terephthalate (PET) film, and place the polyethylene terephthalate (PET) film in deionized water (H2O) after the reaction is completed. 2 O) for 3 min in ultrasonic cleaning, then take out and dry for later use; S2. Preparation of conductive layer: 0.1 mg / mL MXene solution (200 μL) was spin-coated at 5000 rpm on the surface of the polyethylene terephthalate (PET) substrate layer to form a MXene first auxiliary conductive layer; 2 mg / mL silver nanowire (AgNWs) solution (200 μL) was spin-coated at 5000 rpm on the MXene first auxiliary conductive layer to form an AgNWs main conductive layer; 0.1 mg / mL MXene solution (200 μL) was spin-coated at 5000 rpm on the AgNWs main conductive layer again to form a MXene second auxiliary conductive layer, and dried on a heating table at 120°C, and the MXene / AgNWs / MXene flexible transparent conductive film was prepared by annealing process.

[0037] Among them, the MXene nanosheets used to prepare the MXene solution in S2 are Ti 3 C 2 T x .

[0038] Preparation of Ti in S2 3 C 2 T x The specific steps of -MXene are as follows: (1) Add lithium fluoride (LiF) powder into a polytetrafluoroethylene beaker containing 10 mL of hydrochloric acid (HCl) solution (9 M) and stir thoroughly for 30 min to prepare a precursor etching solution; (2) Quantitatively weigh titanium aluminum carbide (Ti 3 AlC 2 ), and add it to the prepared etching solution in small amounts and multiple times, place the reaction system in a 40°C water bath, and stir continuously for 24 hours to obtain a mixed solution; (3) Add a certain amount of deionized water (H 2 O), centrifuge at 3500 rpm for 5 min, pour out the separated supernatant, and add deionized water (H 2 O) and shake until the viscous substance at the bottom is mixed with deionized water (H 2 O) After thorough mixing, continue the centrifugation operation, repeat the operation until the pH of the supernatant is > 6, and then collect the supernatant.

[0039] The preparation method of the silver nanowire (AgNWs) solution in S2 is as follows: (1) Dissolve 1.125 g of polyvinyl pyrrolidone (PVP) in 45 ml of ethylene glycol (C 2 H 6 O 2 ), then add 0.375 g of silver nitrate (AgNO 3 ), wait for silver nitrate (AgNO 3) After the solution is completely dissolved, the resulting liquid is transferred to a flask heated in an oil bath at 160°C; (2) Slowly add 54 mM sodium chloride (NaCl) and 27 mM sodium bromide (NaBr) to the resulting liquid under magnetic stirring. Stir for 10 min after complete addition. Allow the mixed solution to stand for reaction. After the reaction is complete, cool to room temperature. (3) Add acetone (CH 3 COCH 3 ) for purification, the silver nanowires (AgNWs) aggregate and settle, and after filtering out particles and impurities, the silver nanowires (AgNWs) are dispersed in a 0.5wt% polyvinyl pyrrolidone (PVP) aqueous solution, and the purification process is repeated 3-5 times to prepare silver nanowires (AgNWs) with high purity and aspect ratio; (4) Disperse the purified silver nanowires (AgNWs) in anhydrous ethanol (C 2 H 6 O) and prepare the required concentration (2 mg / mL) for later use.

[0040] Example 2 S1. Preparation of substrate layer: Place polyethylene terephthalate (PET) film in 2 wt% polyvinyl pyrrolidone (PVP) aqueous solution, stir at 80 °C, 500 rpm for 1 h, hydrophilize the polyethylene terephthalate (PET) film, and place the polyethylene terephthalate (PET) film in deionized water (H2O) after the reaction is completed. 2 O) for 3 min in ultrasonic cleaning, then take out and dry for later use; S2. Preparation of conductive layer: 0.1 mg / mL MXene solution (200 μL) was spin-coated at 4000 rpm on the surface of the polyethylene terephthalate (PET) substrate layer to form a MXene first auxiliary conductive layer; 4 mg / mL silver nanowire (AgNWs) solution (200 μL) was spin-coated at 4000 rpm on the MXene first auxiliary conductive layer to form an AgNWs main conductive layer; 0.1 mg / mL MXene solution (200 μL) was spin-coated at 4000 rpm on the AgNWs main conductive layer again to form a MXene second auxiliary conductive layer, and dried on a heating table at 120°C, and the MXene / AgNWs / MXene flexible transparent conductive film was prepared by annealing process.

[0041] Among them, the MXene nanosheets used to prepare the MXene solution in S2 are Ti 3 C 2 T x .

[0042] Preparation of Ti in S2 3 C 2 T x The specific steps of -MXene are as follows: (1) Add lithium fluoride (LiF) powder into a polytetrafluoroethylene beaker containing 10 mL of hydrochloric acid (HCl) solution (9 M) and stir thoroughly for 30 min to prepare a precursor etching solution; (2) Quantitatively weigh titanium aluminum carbide (Ti 3 AlC 2 ), and add it to the prepared etching solution in small amounts and multiple times, place the reaction system in a 40°C water bath, and stir continuously for 24 hours to obtain a mixed solution; (3) Add a certain amount of deionized water (H 2 O), centrifuge at 3500 rpm for 5 min, pour out the separated supernatant, and add deionized water (H 2 O) and shake until the viscous substance at the bottom is mixed with deionized water (H 2 O) After thorough mixing, continue the centrifugation operation, repeat the operation until the pH of the supernatant is > 6, and then collect the supernatant.

[0043] The preparation method of the silver nanowire (AgNWs) solution in S2 is as follows: (1) Dissolve 1.125 g of polyvinyl pyrrolidone (PVP) in 45 ml of ethylene glycol (C 2 H 6 O 2 ), then add 0.375 g of silver nitrate (AgNO 3 ), wait for silver nitrate (AgNO 3 ) After the solution is completely dissolved, the resulting liquid is transferred to a flask heated in an oil bath at 160°C; (2) Under magnetic stirring, slowly add 54 mM sodium chloride (NaCl) and 27 mM sodium bromide (NaBr) to the resulting liquid. After complete addition, stir for 10 min. Allow the mixed solution to stand for reaction. After the reaction is complete, cool to room temperature. (3) Add acetone (CH 3 COCH 3 ) for purification, the silver nanowires (AgNWs) aggregate and settle, and after filtering out particles and impurities, the silver nanowires (AgNWs) are dispersed in a 0.5wt% polyvinyl pyrrolidone (PVP) aqueous solution, and the purification process is repeated 3-5 times to prepare silver nanowires (AgNWs) with high purity and aspect ratio; (4) Disperse the purified silver nanowires (AgNWs) in anhydrous ethanol (C 2 H 6O) and prepare the required concentration (4 mg / mL) for later use.

[0044] The light transmittance of the flexible transparent conductive film obtained in Example 1 is 87.1%, the surface resistance is about 9.7Ω / sq, and the maximum heating temperature can reach 69° C. When the film is used for anti-electromagnetic shielding interference, the maximum electromagnetic shielding effectiveness is 25.5dB in the frequency range of 8.2-12.4GHz.

[0045] The light transmittance of the flexible transparent conductive film obtained in Example 2 is 66.7%, and the resistance is about 3.8Ω / sq. The transparent conductive film prepared under this condition is used for a transparent flexible heater, and the temperature reference when the applied voltage is 1V, 2V, 3V, 4V, and 5V respectively Figure 4 , the highest heating temperature can reach 85℃. For anti-electromagnetic shielding interference, see Figure 7 The maximum electromagnetic shielding efficiency in the frequency range of 8.2-12.4GHz is 33.6dB, and the average electromagnetic shielding efficiency is 31.5dB.

[0046] From the above results, we can know that: 1. The light transmittance of the film of Example 2 is slightly lower than that of Example 1 (66.7%), but the surface resistance is lower (3.8Ω / sq), indicating that it has better conductivity. When used as a transparent flexible heater, under low voltage drive (such as 5V), the film can reach a stable high temperature state in a short time, up to 85°C. The maximum heating temperature can reach 85°C. Figure 5 The temperature change trend of the heating film was recorded every 3 minutes when the fixed step voltage was 1V and the voltage range was 1-5V. Figure 5 It can be seen that the film is sensitive to changes in applied voltage and can respond quickly and convert them into temperature changes. At the same time, the results show that the film has good electrical conductivity, the heating performance of the film is proportional to the applied voltage, and the temperature increases with the increase of the applied voltage. The cycle stability experiment is proved by repeatedly switching between 2V and 4V voltage within 80 minutes. When the film prepared in Example 2 is switched between 2V and 4V voltage, it can respond quickly and maintain a constant temperature at the same voltage, highlighting the voltage sensitivity and cycle stability of the film. Figure 6 , when the same voltage is applied, the temperature can reach the same value. It is obvious that the transparent film heater is highly sensitive to voltage.

[0047] 2. The film prepared in Example 2 also performs well in electromagnetic shielding performance. In the frequency range of 8.2-12.4 GHz, the maximum value of electromagnetic shielding efficiency is as high as 33.6 dB, and the average value is 31.5 dB. Figure 8It can be seen that the reflection power coefficient reaches 0.97, the absorption power coefficient is 0.03, and the transmission power coefficient is almost 0, which confirms that the film has a good electromagnetic shielding effect.

[0048] It can be seen from the results of the above embodiments that the high-performance flexible transparent conductive film with a sandwich structure prepared by the present invention exhibits excellent flexibility and electrothermal properties, and has a high electrothermal conversion efficiency. In addition, it also has a high electromagnetic shielding efficiency when used to resist electromagnetic shielding interference.

[0049] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A multifunctional flexible transparent conductive film, characterized in that: It includes a polyethylene terephthalate base layer and a conductive layer, wherein the conductive layers are, from bottom to top, a MXene first auxiliary conductive layer, a silver nanowire main conductive layer and a MXene second auxiliary conductive layer.

2. A method for preparing a multifunctional flexible transparent conductive film, characterized in that: The following steps are involved: S1. Preparation of substrate layer: placing a polyethylene terephthalate film in a polyvinyl pyrrolidone aqueous solution, stirring at 60-80° C. for 0.5-1 h, hydrophilizing the polyethylene terephthalate film, and after the reaction is completed, washing the polyethylene terephthalate film with anhydrous ethanol and deionized water and drying it to prepare a polyethylene terephthalate substrate for standby use; S2. Preparation of conductive layer: Spin-coat MXene solution, silver nanowire solution and MXene solution layer by layer on the surface of polyethylene terephthalate substrate layer, and dry on a heating table to obtain a transparent and flexible conductive film.

3. The method for preparing a multifunctional flexible transparent conductive film according to claim 2, characterized in that: The molecular weight of polyvinyl pyrrolidone used in S1 is 1300000, and the concentration of the prepared aqueous solution is 1-4wt%.

4. The method for preparing a multifunctional flexible transparent conductive film according to claim 3, characterized in that: The MXene nanosheets used to prepare the MXene solution in S2 are Ti3C2T x .

5. The method for preparing a multifunctional flexible transparent conductive film according to claim 4, characterized in that: Preparation of Ti3C2T in S2 x The specific steps of -MXene are as follows: (1) adding lithium fluoride powder into a polytetrafluoroethylene beaker containing a hydrochloric acid solution and stirring to prepare a precursor etching solution; (2) Weighing aluminum titanium carbide quantitatively, and adding it to the precursor etching solution in small amounts and multiple times, placing the reaction system in a 40°C water bath, stirring continuously, to obtain a mixed solution; (3) Add a certain amount of deionized water to the obtained mixed solution and centrifuge it. Pour out the separated supernatant, add deionized water again and shake it to mix with the viscous material at the bottom. Continue centrifugation. Repeat the operation until the pH of the supernatant is >6, and collect the supernatant.

6. The method for preparing a multifunctional flexible transparent conductive film according to claim 5, characterized in that: In step (3), the centrifugal speed is 1500-3500 rpm and the centrifugal time is 3-5 min.

7. The method for preparing a multifunctional flexible transparent conductive film according to claim 2, characterized in that: The preparation method of the silver nanowire solution in S2 is: (1) Dissolve polyvinyl pyrrolidone in ethylene glycol, then add silver nitrate. After the silver nitrate is completely dissolved, transfer the resulting liquid to a flask and heat it in an oil bath; (2) Under magnetic stirring, slowly add sodium chloride and sodium bromide, then stir to mix, let stand to react, and cool to room temperature after the reaction is complete; (3) adding acetone to the silver nanowires to cause them to aggregate and settle, filtering out particles and impurities, and dispersing the silver nanowires in a 0.5 wt % polyvinyl pyrrolidone aqueous solution, repeating this process 3-5 times to obtain purified silver nanowires; (4) Disperse the purified silver nanowires in anhydrous ethanol and prepare the required concentration for later use.

8. The method for preparing a multifunctional flexible transparent conductive film according to claim 7, characterized in that: In step (2), the concentration of sodium chloride is 22-54 mM, and the concentration of sodium bromide is 10-27 mM.

9. The method for preparing a multifunctional flexible transparent conductive film according to claim 2, characterized in that: The spin coating speed of the MXene solution in S2 is 4000-5000 rpm for 20-50 s, and the spin coating speed of the silver nanowires is 3000-5000 rpm for 30-50 s.

10. The method for preparing a multifunctional flexible transparent conductive film according to claim 2, characterized in that: The concentration of the MXene solution is 0.1-0.5 mg / mL, and the concentration of the silver nanowire solution is 2-4 mg / mL.

Citation Information

Patent Citations

  • Flexible transparent conductive film of two-dimensional transition metal carbide-carbonitride Ti3C2Tx-MXene template method electrochemical deposition nickel nanoparticle and preparation method of flexible transparent conductive film of two-dimensional transition metal carbide-carbonitride Ti3C2Tx-MXene template method electrochemical deposition nickel nanoparticle

    CN118290800A

Cited By

  • Flexible electrode based on silver nanowire and polyethyleneimine and preparation method thereof

    CN121583649A